2020
DOI: 10.1093/cid/ciaa355
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evolution of AmpC-Mediated Ceftazidime-Avibactam and Cefiderocol Resistance in Enterobacter cloacae Complex Following Exposure to Cefepime

Abstract: We report 2 independent patients from whom carbapenem and ceftazidime-avibactam–resistant Enterobacter cloacae complex strains were identified. The ceftazidime-avibactam resistance was attributed to a 2–amino acid deletion in the R2 loop of AmpC β-lactamase, which concurrently caused resistance to cefepime and reduced susceptibility to cefiderocol, a novel siderophore cephalosporin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 15 publications
1
48
0
Order By: Relevance
“…Shields and colleagues demonstrated a 2–amino acid deletion in the R2 loop of the AmpC β-lactamase (ie, alanine and leucine at positions 292 and 293) in 2 Enterobacter hormaechei isolates from distinct patients after exposure to cefepime [ 9 ]. These deletions appear to broadly impact cephalosporin antibiotics in that they confer resistance to cefepime, CAZ-AVI, and cefiderocol—in the absence of preceding exposure to CAZ-AVI or cefiderocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shields and colleagues demonstrated a 2–amino acid deletion in the R2 loop of the AmpC β-lactamase (ie, alanine and leucine at positions 292 and 293) in 2 Enterobacter hormaechei isolates from distinct patients after exposure to cefepime [ 9 ]. These deletions appear to broadly impact cephalosporin antibiotics in that they confer resistance to cefepime, CAZ-AVI, and cefiderocol—in the absence of preceding exposure to CAZ-AVI or cefiderocol.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins associated with increased permeability were also assessed (OprD, mex-operon encoded proteins). Furthermore, based on reports of deletions, insertions, and amino acid substitutions in or proximal to the omega loop of AmpC contributing to cefiderocol resistance [ 9–11 ], this region was carefully examined. Bioinformatics analyses were conducted by Ares Genetics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 4- to 32-fold increase of an MIC90 was observed in D179Y-H274Y mutations of KPC-31 compared to the wild-type alleles reported by Hobson et al in 2021 ( 35 ). Shields et al have reported that the deletion of positions 292 and 293, which are located in the R2 loop of AmpC, causes the decreased susceptibility of Enterobacterales ( 38 ). The mutations lead to the disappearance of the H10 helix in the R2 loop and the expansion of the substrate-binding site, resulting in a more stable binding to the bulkier side chain possessed by CFDC ( 38 ).…”
Section: Resistance Mechanismsmentioning
confidence: 99%
“…Shields et al have reported that the deletion of positions 292 and 293, which are located in the R2 loop of AmpC, causes the decreased susceptibility of Enterobacterales ( 38 ). The mutations lead to the disappearance of the H10 helix in the R2 loop and the expansion of the substrate-binding site, resulting in a more stable binding to the bulkier side chain possessed by CFDC ( 38 ). Akito et al have demonstrated the alanine-proline deletion at positions 294 and 295 located in the R2 loop, which is also associated with the reduced susceptibility to CFDC in E. coli and E. cloacae ( 39 ).…”
Section: Resistance Mechanismsmentioning
confidence: 99%